1990
DOI: 10.1002/jcla.1860040411
|View full text |Cite
|
Sign up to set email alerts
|

Current status of clinical laboratory tests for the human immunodeficiency virus

Abstract: The predictive values of positive and negative test results for human immunodeficiency virus (HIV) antibody are extremely high in laboratories that have good quality control and high performance standards and use licensed FDA-approved enzyme immunoassay (EIA) and Western blot standardized tests. With a carefully designed protocol, the false-positive rate of combined EIA and Western blot has been reported to be as low as 1 in 10(5). When results of HIV confirmatory antibody tests are indeterminate, other tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…In summary, the new anti-HIV 1 and 2 test is highly suited for anti-HIV screening. The flexibility of the test concept allows discrimination between HIV-1 and HIV-2; thus, the newly developed anti-HIV 1 and 2 test has the additional features of being able to diagnose HIV infection and may contribute to a reduction in the spread of this deadly disease (2,15,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, the new anti-HIV 1 and 2 test is highly suited for anti-HIV screening. The flexibility of the test concept allows discrimination between HIV-1 and HIV-2; thus, the newly developed anti-HIV 1 and 2 test has the additional features of being able to diagnose HIV infection and may contribute to a reduction in the spread of this deadly disease (2,15,18).…”
Section: Discussionmentioning
confidence: 99%
“…An additional important tool that can be used to reduce the spread of HIV is the early and reliable recognition of the HIV infection by sensitive tests (15). The anti-HIV 1 and 2 test has been shown to reduce significantly the risk of HIV infection by blood and blood products (2,15,18). The test is also able to identify HIV-infected persons, allowing them to adjust their behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…has been greatly reduced since the development of appropriate screening methods for antibodies to HIV (anti-HIV) in blood banks (5)(6)(7)(8). In 1985 two patients were hospitalized in Europe with an initial diagnosis of acquired immune deficiency syndrome (AIDS) based on clinical symptoms, but they were nonreactive for antibodies to HIV by enzyme immunoassay (ELISA) and showed indeterminate Western blot patterns (9).…”
Section: Human Immunodeficiency Virus (Hiv) Infection Via Blood Transmentioning
confidence: 99%
“…To reduce the chances of technical or clerical error, the antibody tests are confirmed by additional tests like ELISA, western blot, and PCR analysis. When tests are combined, for example, ELISA and western blot, the false-positive rate has been reported to be as low as 1/100 000 [ 3 ]. Others have indicated that even when tests are combined, about 3% of the investigated sera were false-positive, false-negative, or noninterpretable [ 4 ].…”
Section: Introductionmentioning
confidence: 99%